The coming multi-order world. Issue 1 (2nd January 2016) - Flockhart, Trine
ABSTRACT: The article shows that the current international system is changing towards a completely new form of international system, conceptualized as a multi-order system. The suggestion for a multi-order world stands in contrast to three current narratives about the future global order expressed through a multipolar narrative; a multi-partner narrative and a multi-culture narrative. The article demonstrates that although each narrative points to a plausible future, neither fully captures what lies ahead. Using English School concepts such as order, international society, international system and primary and secondary institutions, the article reveals a conception of the coming international system as a system consisting of several different 'orders' (or international societies) nested within an overall international system. In the coming 'multi-order world', the liberal order will continue, and may even be strengthened internally, but its global reach will be a thing of the past. Moreover, the challenge in a multi-order world will be to forge new forms of relationships between composite and diverse actors across complex lines of division and convergence. Scholars and policy-makers should note that the coming multi-order world will be radically different, requiring new thinking and new institutions and the acceptance of diversity in both power and principle.